Evaluation of Serum/Urine Genomic and Metabolomic Profiles to Improve the Adherence to Sildenafil Therapy in Patients with Erectile Dysfunction - Rocca, Maria Santa; Vignoli, Alessia; Tenori, Leonardo; Ghezzi, Marco; De Rocco Ponce, Maurizio; Vatsellas, Giannis; Thanos, Dimitris; Padrini, Roberto; Foresta, Carlo; De Toni, Luca (Frontiers in Pharmacology, 2020)
Type V-phosphodiesterase-inhibitors (PDE5i) are the first choice drugs in the treatment of erectile dysfunction (ED), being effective in 60-70% of patients. However, approximately 50% patients per year discontinue the treatment with PDEi after reporting poor drug efficacy or major adverse drug reactions (ADR). In order to identify early markers of efficacy/safety for the treatment of ED with PDE5i, the basal clinical characteristics of patients, integrated with metabolomics analysis of serum and urine and genomic data, were here correlated with the PDE5i efficacy and the occurrence ADR upon administration. Thirty-six males with new diagnosis of ED were consecutively recruited and characterized at baseline for anthropometrics, blood pressure, blood glucose, lipid profile, serum levels of thyroid/sex hormones and erectile function evaluated by IIEF-15 questionnaire. Targeted Next Generation Sequencing (NGS) was applied to genes involved in PDE5i pharmacodynamics and pharmacokinetics. Fasting metabolic profile of serum and urine were assessed by nuclear magnetic resonance (NMR)-based metabolomics analysis. Patients were prescribed on-demand therapy with Sildenafil oro-dispersible film and followed-up after 3 months from recruitment. Baseline data were compared with IIEF-15 score at follow-up and with the occurrence of ADR recorded by a dedicated questionnaire. Twenty-eight patients were finally included in the analysis. Serum LDL-cholesterol levels were increased in those reporting ADR (143.3 ± 13.2 mg/dL ADR vs 133.1 ± 12.4 mg/dL No ADR; P = 0.046). NGS data showed that specific variants of PDE11A and CYP2D7 genes were more represented in drug responders (both relative risk=2.7 [0.9-5.1]; P=0.04). NMR-based metabolomics showed the highest association between serum LDL-cholesterol metabolites and the occurrence of ADR (Hazard ratio = 17.5; P=0.019). The association between lipid profile and the ADR pattern suggests major cues in the tailoring of ED therapy with PDE5i.